The performance analysis of amplitude suppression of sinusoidal hindrances - V. A. Danilov; L. V. Danilova (Известия высших учебных заведений России: Радиоэлектроника)
The problem of the performance analysis of non-Gaussian amplitude suppression with distribution of envelope is considered. The asymptotic values of the characteristics are investigated. The efficiency of simplified processing of envelope of accepted oscillations is determined. The analysis of amplitude suppression of sinusoidal hindrance with harmonic vibration with free angle modulation is conducted. The influence of hindrance with radio- and video-frequency spectrum is considered separately. The situation when the spectrum of signal and the spectrum of hindrance are commensurable numbers is analyzed. The asymptotic analysis of characteristics of amplitude suppression efficiency which corresponds to the infinitely large value of the parameter of the non-Gaussian hindrance distribution is presented. The efficiency of applying of simplified processing of envelope of accepted oscillation is analyzed.